Z-plasty and Postoperative Radiotherapy for Upper-arm Keloids: An Analysis of 38 Patients. Issue 11 (November 2019) - Dohi, Teruyuki; Kuribayashi, Shigehiko; Tosa, Mamiko; Aoki, Masayo; Akaishi, Satoshi; Ogawa, Rei
Abstract : Background: Therapies for upper arm keloids include surgical excision followed by postoperative radiotherapy, silicone tape stabilization, and steroid plaster. However, a universally accepted therapeutic strategy for upper-arm keloids is lacking. Methods: All consecutive patients with single upper-arm keloids who underwent keloid excision followed by tension-reducing suturing, multiple z-plasties, and postoperative radiotherapy in 2013–2016 in the keloid/scar specialist clinic at the Department of Plastic, Reconstructive and Aesthetic Surgery of Nippon Medical School, were included in this case series study. Only keloids that arose from the small injury produced during Bacillus Calmette–Guérin vaccination were selected. The postsurgical radiotherapy regimen was 18 Gy administered in 3 fractions over 3 days. Radiotherapy was followed by tension-reducing wound self-management with silicone tape and, if needed, steroid plaster. The primary study objective was keloid recurrence during the 24-month follow-up period. Recurrence was defined as the growth of stiff red lesions in even small areas of the scar that was refractory to at least 2 months of steroid plaster therapy. Results: In total, 38 patients with 38 lesions were enrolled. Two lesions (5.3%) recurred. Both recurrences were successfully treated by concomitant steroid plaster and steroid injection. The recurrence patients were significantly more likely than the nonrecurrence patients to have multiple keloids. The 2 groups did not differ in terms of original keloid size. Conclusions: Upper-arm keloids can be successfully treated by customized plans that involve appropriate surgical modalities (including multiple z-plasties), postoperative radiotherapy (18 Gy/3 fractions/3 d), and postoperative wound/scar self-management with silicone tape and steroid plaster.